2000
DOI: 10.1007/s003300050010
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic digit: an uncommon developmental anomaly

Abstract: The radiological features of seven cases of pelvic digit discovered incidentally on plain radiographs are described and differentiation from other causes of new bone formation is discussed. Its recognition as a benign anomaly is important to avoid unnecessary investigation or intervention. An embryological theory of development of pelvic digit is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 11 publications
0
19
0
2
Order By: Relevance
“…McGlone et al (4) reported seven cases that were identified during intravenous urography; none of the patients had symptoms related to the pelvic digit. Van Breuseghem (5) described a patient with breast cancer whose pelvic digit was detected during screening for metastases; emphasis was placed on the importance of its radiologic recognition.…”
Section: Discussionmentioning
confidence: 99%
“…McGlone et al (4) reported seven cases that were identified during intravenous urography; none of the patients had symptoms related to the pelvic digit. Van Breuseghem (5) described a patient with breast cancer whose pelvic digit was detected during screening for metastases; emphasis was placed on the importance of its radiologic recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Cette anomalie osseuse congénitale rare peut survenir à n'importe quel niveau des os pelviens, et peut même être localisée entière-ment à l'intérieur des tissus mous de la paroi abdominale [2,4]. Occasionnellement, l'anomalie peut être bilatérale ou multiple [5,6]. Elle est généralement asymptomatique et découverte seulement fortuitement [7].…”
Section: Discussionunclassified
“…Généralement, son aspect est celui d'une côte ou d'une phalange avec une ou plusieurs articulations ou pseudoarticulations internes, comme dans le cas présent [6]. L'anomalie présente souvent une pseudo-articulation avec le squelette axial à sa base.…”
Section: Discussionunclassified
“…Although most commonly referred to as a "digit", the phalynx-like structure is hypothesized to arise from anomalous rib tissue [58,59]. Pelvic digits typically arise adjacent to the iliac bones but have been reported adjacent to the sacrum, coccyx, anterior abdominal wall, and the symphysis pubis.…”
Section: Pelvic Digitmentioning
confidence: 99%